Elevated levels of neutrophils with a pro-inflammatory profile in Turner syndrome across karyotypes - Jesper Just; Lukas Ochsner Reynaud Ridder; Emma Bruun Johannsen; Jens Magnus Bernth Jensen; Mikkel Steen Petersen; Helene Viborg Christensen; Kenneth Kjærgaard; Jacob Redder; Simon Chang; Kirstine Stochholm; Anne Skakkebæk; Claus Højbjerg Gravholt (npj Genomic Medicine)
Abstract Turner syndrome (TS) presents with multiple karyotypes, including 45,X monosomy and variants such as isochromosomes and mosaicism, and is characterized by several co-morbidities, including metabolic conditions and autoimmunity. Here, we investigated the genomic landscapes across a range of karyotypes. We show that TS have a common autosomal methylome and transcriptome, despite distinct karyotypic variations. All TS individuals lacked the X chromosome p-arm, and XIST expression from the q-arm did not affect the autosomal transcriptome or methylome, highlighting the critical role of the missing p-arm with its pseudoautosomal region 1. Furthermore, we show increased levels of neutrophils and increased neutrophil activation. The increase in neutrophils was linked to TS clinical traits and to increased expression of the X-Y homologous gene TBL1X, suggesting a genetic basis, which may lead to neutrophil-driven inflammatory stress in TS. Identifying TS individuals with increased neutrophil activation could potentially mitigate the progression towards more severe metabolic issues.